Pentingnya penerapan desain yang inklusif di dalam bangunan - Chairina, Fitra (Maliki Interdisciplinary Journal, 2024)
The application of inclusive design in buildings is crucial to create environments that are accessible and usable by all individuals, including those with disabilities. Inclusive design emphasizes not only aesthetic aspects, but also accessibility and comfort for all users. This article discusses how inclusive design can eliminate physical and social barriers, so that everyone can participate equally in various activities in public and private spaces. By considering various elements such as lighting, ventilation, and user-friendly material selection, inclusive design contributes to the creation of spaces that support diversity. In addition, this article emphasizes the importance of involving the community in the design process to ensure that the needs of all users are met. Through the application of inclusive design principles, it is hoped that buildings can be realized that are not only functional but also inclusive, so that every individual feels valued and has the same rights to access facilities. Thus, inclusive design plays an important role in supporting the sustainable development goals (SDGs) and creating a more just and equal society.